Developing family interventions for adolescent HIV prevention in South Africa. (24th March 2016) - Kuo, Caroline; Atujuna, Millicent; Mathews, Catherine; Stein, Dan J.; Hoare, Jacqueline; Beardslee, William; Operario, Don; Cluver, Lucie; K. Brown, Larry
ABSTRACT: Adolescents and young people account for 40% of all new HIV infections each year, with South Africa one of the hardest hit countries, and having the largest population of people living with HIV. Although adolescent HIV prevention has been delivered through diverse modalities in South Africa, and although family-based approaches for adolescent HIV prevention have great potential for highly affected settings such as South Africa, there is a scarcity of empirically tested family-based adolescent HIV preventive interventions in this setting. We therefore conducted focus groups and in-depth interviews with key informants including clinicians, researchers, and other individuals representing organizations providing HIV and related health services to adolescents and parents ( N  = 82). We explored family perspectives and interactions around topics such as communication about sex, HIV, and relationships. Participants described aspects of family interactions that presented both challenges and opportunities for family-based adolescent HIV prevention. Parent–child communication on sexual topics were taboo, with these conversations perceived by some adults as an invitation for children to engage in HIV risk behavior. Parents experienced social sanctions for discussing sex and adolescents who asked about sex were often viewed as disrespectful and needing discipline. However, participants also identified context-appropriate strategies for addressing family challenges around HIV prevention including family meetings, communal parenting, building efficacy around parent–adolescent communication around sexual topics, and the need to strengthen family bonding and positive parenting. Findings indicate the need for a family intervention and identify strategies for development of family-based interventions for adolescent HIV prevention. These findings will inform design of a family intervention to be tested in a randomized pilot trial (ClinicalTrials.gov #NCT02432352).